(untitled) (Research, Society and Development, 2020)
Batak Toba people are formed from kinship patrilineal systems which follow men side in lineage. Therefore, the position of men is more important than women. Traditional marriage of Batak Toba people is honest marriage where men relative has to pay certain amount of money or it usually called as bride-price to women relative. People of Batak Toba explained that honest marriage is a principal, beliefs and an attitude of magis religious (relationship between spiritual thing and their beliefs). The most important requirement for pauseang-field is honest marriage and giving bride-price (sinamot/tuhor). Bride-price must be fully paid by men relatives to women relatives. There is a consequences if men’s relative are not fully paid the money, men’s relative will have customary debt and must be done as traditional duty. Therefore, pauseang-field cannot be given to daughter and her husband. Tanah pauseang-field from parent (father) will be managed by her husband, because in Batak Toba, daughter could not own any inheritance.